Carrie Soto is Back - Reid, Taylor Jenkins (New York : Ballantine Books, 2022)
"In this powerful novel about the cost of ambition and success, a legendary athlete attempts a comeback at an age when the world considers her past her prime-from the New York Times bestselling author of Malibu Rising. Carolina Soto is undeniably fierce. She is determined to be the best professional tennis player the world has ever seen. And by the time she retires from the game in 1989 at the age of thirty-one, she is just that: the best. She has shattered every record and claimed twenty Slam titles. And if you ask Carrie, she is entitled to every one of those victories. After all, her dad-a former champion tennis player himself-has trained her for this since the age of two, always emphasizing, "We don't stop for one second until you are the best." Which is why it is infuriating when Nicki Chan arrives on the scene six years later and ties Carrie with twenty Slams. Just like that, Carrie's championship record is slipping through her hands. And she can't let that happen. So at thirty-seven years old, Carrie Soto is coming out of retirement to defend her title. Even if the sports media says she's too old to be playing professionally. Even if her injured athlete's body doesn't move as fast as it once did. Even if it means trusting her father to coach her again after he betrayed her all those years ago. And even if the fans don't want the cold, heartless "Battle Axe" Carrie back. In spite of it all: Carrie. Is. Back. She will return for one final season to prove to the world that she is the all-time champion. Because if you know your destiny is to be the best, isn't it your right to keep fighting for it?"--
Keywords: Tennis players -- Fiction; Fathers and daughters -- Fiction; Novels